Behavioral risk factors in oncology patients: A matched case control study from Yemen - Mansour Abdu Al-Taj; Arzaq Mohammed Al-Salahi; Asad Ali Al-Salami; Aya Lutf Aldhurafi; Essa Mohammed Ghaliah; Jalila Abdulsalam Al-Yarimi; Majdi Abdullah Al-Rosi; Rashed Hussien Ahmed; Sara Abdullah Al-Jrrash; Tasneem Fuad Al-Sabri (PLoS ONE, 2025)
Background Cancer is a significant public health challenge globally, marked by the uncontrolled growth of abnormal cells that can lead to severe morbidity and mortality. Modifiable lifestyle factors significantly influence cancer risk. The study aimed to investigate the behavioral risk factors of cancer among Yemeni adults, highlighting the critical need for targeted prevention strategies. Methods A matched case-control study design was used. It carried out at the National Center of Oncology in Sana’a, Yemen, and the largest referral center for cancer patients in Yemen. The study included 680 participants, consisting of 340 newly diagnosed cancer cases and 340 matched controls. Controls matched cases on age, sex, and place of resident. All subjects volunteered to participate and were personally interviewed using a structured questionnaire that covered socio-demographic, behaviors and dietary intake data. Crude odd ratios (COR) and adjusted odds ratios (AOR) were estimated using conditional logistic regression and the level of significance was set at p-value < 0.05. Results Our analysis found that those who have any family member with a history of cancer (AOR = 2.84; 95% confidence interval (CI): 1.59–5.06), consuming bread or food made from white flour more than once a day (AOR = 2.21; 95% CI: 1.03–4.73), frequently consuming animal oil three to seven times per week (AOR = 3.43; 95% CI: 1.76–6.70), and consuming soft drinks three to seven times per week (AOR = 2.08; 95% CI: 1.08–4.01) were at higher risk of cancer. However, those who had no formal work but supporting family activities (AOR = 0.35; 95% CI: 0.15–0.79), consuming fruit frequently during its seasons (AOR = 0.25; 95% CI: 0.09–0.67), consuming coffee three to seven times (AOR = 0.36; 95% CI: 0.21–0.62) or one to two times per week (AOR = 0.44; 95% CI: 0.23–0.81) were less likely to have cancer. Additionally, no significant differences found between cases and controls regarding education level, smoking, chewing shamma, and frequent consumption of other food and beverages. Conclusion Frequent consumption of bread or products made from white flour, animal fats, and soft drinks were statistically associated with cancer. On the contrary, moderate coffee consumption and frequent intake of seasonal fruits showed to be protected from cancer. Additionally, a family history of cancer was identified as a significant risk factor for developing the disease. To mitigate cancer risk in Yemen, implementing health education campaigns through media to promote awareness of these dietary influences are needed. Additionally, community initiatives should encourage healthier eating habits, emphasizing the importance of fresh fruits and moderate consumption of coffee, and reducing the intake of food made from white flour, animal fat and sugary beverages.